PELAKSANAAN PENERIMA KARTU PERLINDUNGAN SOSIAL (KPS) DI KENAGARIAN PUNGGASAN KECAMATAN LINGGO SARI BAGANTI (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2016)
This study aims to identify and analyze the implementation of the card recipient social protection (KPS) in Punggasan village Linggo Sari Baganti District Pesisir Selatan region of: 1) the condition of beneficiary households KPS, 2) Family income recipients KPS and, 3) the availability of water and sanitation family KPS recipients.This type of research is quantitative descriptive. The study population numbered 93 families, whereas for sampling study using total sampling of the number of recipients of total tamplingwith the number 93 KK. Data obtained from the relevant agencies, namely, Pesisir Selatan region Social Service, and the results of the field survey.The results showed as follows; 1) The condition of the home receiver KPS in Punggasan village Linggo Sari Baganti District generally uniform, the roofs of zinc, walls and floors of cement, sources of electric lighting, ventilation generally one for each room, a place to store food in a clean, storing food in a clean and not separated and activities MCK in private bathrooms, 2) Income recipients KPS generally <Rp 500,000 / month, a side job only occasionally, other family members who have an income is the wife, the average expenditure for staples <Rp 500,000 / month and expenses in addition to the basic needs of an average of Rp 100,000 - Rp 200,000 / month and, 3) The provision of clean water KPS recipients generally well, clear water, fresh taste. treatment of water reservoirs clean by draining clean water reservoirs, treatment is done 1 time in 1 week, and the distance of the source of clean water with sewage disposal is generally 25-50 meters.Key Words: implementation, the social protect, KPS